Fuzzy modelling of load and cost uncertainties and their impact on power systems operation
Power systems are nowadays, more than ever, affected by uncertainties of multiple origins, such as physical, technical, economic, regulatory, political and environmental. Together, they create huge volatility associated with generation electricity prices, demand and generation capacity. As a result, modeling uncertainties in power systems is once again on the top of the agenda of researchers that aim at giving positive answers to the new requirements of the systems. In this sense, in this paper we are enlarging the original Fuzzy Optimal Power Flow, FOPF, model in order to consider not only load uncertainties, but also uncertainties in generation costs, specified using trapezoidal fuzzy numbers. This new approach is based on multiparametric linear programming techniques that lead to the identification of a number of critical regions covering all the uncertainty space contributing to build more accurate membership functions of all variables, namely generations, branch flows and power not supplied. The paper includes results of a case study based on the IEEE 24 bus test system to illustrate the application of the developed approach.